1985
DOI: 10.1002/jmv.1890170206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness among human rotaviruses

Abstract: The genetic relatedness of 81 clinical rotavirus isolates to the human rotavirus prototype strains Wa (subgroup 2, serotype 1) and DS-1 (subgroup 1, serotype 2) was examined by RNA hybridization techniques. Labeled single-stranded (+) transcripts of Wa or DS-1 virus were incubated with denatured genomic rotaviral RNAs, and the resulting hybrids were subjected to gel electrophoresis and autoradiography. Nineteen of the specimens contained subgroup 1 rotavirus with a "short" RNA migration pattern. These viruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 16 publications
3
52
0
Order By: Relevance
“…Variation in genome profile does not always correlate with antigenic variation or with variation in nucleotide sequence. 7,9,12 An early study on reovirus indicated a single base change within an RNA segment resulted in a detectable change in the migration of that segment. 13 Conversely, segments with different nucleotide sequences may exhibit similar electrophoretic mobilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in genome profile does not always correlate with antigenic variation or with variation in nucleotide sequence. 7,9,12 An early study on reovirus indicated a single base change within an RNA segment resulted in a detectable change in the migration of that segment. 13 Conversely, segments with different nucleotide sequences may exhibit similar electrophoretic mobilities.…”
Section: Discussionmentioning
confidence: 99%
“…13 Conversely, segments with different nucleotide sequences may exhibit similar electrophoretic mobilities. 7,12,28 Correlation of electropherotype and serotype in porcine rotaviruses has been hampered by technical prob- Table 3. Variation in migration pattern in each RNA genome segment of field viruses as compared with the migration of corresponding segments of prototype OSU and Gottfried porcine rotaviruses in coelectrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…Cocirculation of different electropherotypes or replacement of one by another have been found in many parts of the world (Espejo et al 1980;Rodger et al 1981;Schnagl, Rodger & Holmes, 1981;Lourenco et al 1981;Flores et al 1982;Pereira et al 1983;Follett & Desselberger, 1983 a). At present it is not quite clear how these differences emerge and what their significance is.…”
Section: Discussionmentioning
confidence: 99%
“…RNA migration patterns ('electropherotypes', Rodger et al 1981, Schnagl, Rodger & Holmes, 1981; 'electrophoretypes', Thouless, Beards & Flewett, 1982) can thus be determined. Rotaviruses of different RNA migration pattern were isolated from infected children in different areas of the world either sequentially Schnagl, Rodger & Holmes, 1981) or at the same time (Espejo et al 1980;Rodger et al 1981;Flores et al 1982;Follett & Desselberger, 1983a).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that human rotaviruses can be placed together in terms of their gene homology and have proposed to term such genetic classifications of rotaviruses "genogroup" (15) instead of "family" (3,4), so that the classification can conform to the taxonomic hierarchy. Thus, it was recently shown by RNA-RNA hybridization that human rotaviruses fall into any one of three distinct genogroups (13) ; i.e., the first genogroup that includes strains related to the Wa strain (serotype 1, subgroup II, long RNA electropherotype) ; the second genogroup that includes strains related to the DS-1 strain (serotype 2, subgroup I, short RNA electropherotype) ; and the third genogroup that includes strains related to the AU-1 strain (serotype 3, subgroup I, long RNA electropherotype).…”
Section: T Nakigomi Et Almentioning
confidence: 99%